Implementation of the UNCLOS 1982 in Utilization of Highly Migratory Species By Indonesia - Usmawadi Usmawadi (Faculty of Law, Sriwijaya University, Indonesia, 2020)
Indonesia is one of the producers of tuna and tuna species (tuna, skipjack, and mackerel tuna), which are increasing every year. Its geographical location and area of its many Exclusive Economic Zones (EEZs) bordering many neighboring countries, requires Indonesia to implement the CLS 1982 provisions on far-migratory fish. In this connection, Indonesia implements two forms. Firstly, in the form of legislation, which Indonesia has issued about 17 regulations, starting from the level of the Law to the Ministerial Regulation. Secondly, Indonesia has been active as a member of regional fisheries organizations whose territory borders on the Indonesian EEZ. Consequently, from the issuance of this Ministerial Regulation, Indonesia must carry out fisheries monitoring on board, to meet the higher quality data needs. So that Indonesia is faced with carrying out monitoring on fishing vessels operating in the convention area of the RFMOs, namely the Indian Ocean Tuna Commission, the Commission for Southern Blue Fin Tuna Conservation, and the Central and Western Pacific Fisheries Commission. In order to optimize this implementation, Indonesia needs to prepare officials, facilities, and infrastructure that can support the compliance and enforcement of legislation that has been issued. Indonesia should immediately formulate fisheries policies in the high seas outside the Indonesian EEZ, which involve and benefit Indonesian fishermen.